Impact of the 1988 disengagement decision on the Palestinian cause - Saadeh, Alaa Kamel; Ibrahim Al-Hajj, Abdulmajid Ali; Al-Sarhan, Khader Eid; Khasawneh, Asma Jadallah; Al-Atawi, Ikhlas Khalaf; Al-Shiyab, Abdullah Ahmad (Research Journal in Advanced Humanities, 2026)
This research aims to study the results and effects of the legal and administrative disengagement decision on the Palestinian cause, both locally and internationally. This includes examining its impact on supporting the Palestinian national movement, highlighting Palestinian identity, and striving for Palestinian independence and the establishment of a Palestinian state on Palestinian soil—all of which serve the interests of the Palestinian cause and the Arab Palestinian people. The research employs a descriptive historical approach, based on collecting and analyzing primary sources, namely speeches by His Majesty King Hussein related to the disengagement decision, as well as other relevant references. These sources are then studied and analyzed. The legal and administrative disengagement decision was intended to highlight the Palestinian cause from an Arab perspective, supporting and striving for Palestinian independence and statehood, given that the Palestine Liberation Organization (PLO) is the sole legitimate representative of the Palestinian people. Conferences held in several Arab cities and Arab summits contributed to pressuring Jordan to issue the disengagement decision, which actually occurred in 1988. However, despite this decision, the Palestinian issue remains an Arab, international, and global issue, representing the right of the Palestinian people, who continue to demand their legitimate right to establish their state on the occupied Palestinian land.